Hábitos forrajeros de Ammotragus lervia (Pallas, 1777) (Artiodactyla: Bovidae) en matorral desértico rosetófilo de Coahuila, México - Gastelum-Mendoza, Fernando Isaac; González-Saldívar, Fernando Noel; Lozano-Cavazos, Eloy Alejandro; Uvalle-Sauceda, José Isidro; Serna-Lagunes, Ricardo; Cantú-Ayala, César Martín (Instituto de Ecología, A.C., 2023)
The barbary sheep (Ammotragus lervia Pallas, 1777) is an exotic herbivore considered an invasive species in northeastern Mexico, for which the effects of herbivory on native vegetation and competition with native ungulates are unknown. The objective of the study was to identify the composition and seasonal diversity of the diet of a population of A. lervia in the UMA Rancho San Juan, municipality of Monclova, Coahuila, Mexico. During the period October 2018-August 2019, lines were established where the fecal samples were collected, processed and classified, and a photographic catalog of plant cell structures of the plants present in the habitat was generated. Using the microhistological technique, the species of plants consumed were identified and classified by season: autumn (October 2018), winter (February 2019), spring (May 2019) and summer (August 2019) and biological form (shrubs, herbaceous, grasses and succulents). The diet was expressed in relative frequency based on the Fracker and Brischle table. The diversity of the diet was estimated with the Shannon index. In the diet of A. lervia, 64 species and 21 families were identified, being the families Poaceae (15), Fabaceae (9 spp.), Asteraceae (8 spp.) and Euphorbiaceae (7 spp.) the most representative. Likewise, Vachellia rigidula, Tiquilia canescens, Medicago sativa and Opuntia engelmannii together represented 46.49% of the diet. In the year, the diet was made up of 36% shrubby plants, 30% herbaceous, 22% grasses and 12% succulents. Shrubs predominated in spring (54.80%), herbaceous plants (46.39 and 37.90%, respectively) in summer and winter, and grasses (35.19%) in autumn. The diversity of the diet was H’ = 2.89 ± 0.13 species, higher than that reported in its natural habitat. The composition of the diet of A. lervia was similar to that reported for other wild herbivores of desert scrub in Mexico and the United States, this implies a condition of overlapping diet, but more studies on the diet of sympatric herbivores of northeastern Mexico are required.